Consuming Ecstasy: Representations of Male and Female Orgasm in Mainstream Pornography - Séguin, Léa J.; Rodrigue, Carl; Lavigne, Julie (The Journal of Sex Research, 2018)
Social representations, which appear in a variety of media, can influence the way sexual experiences are perceived and understood. While pornography is not the only medium in which orgasm is portrayed, it is the most explicit, and it is widespread and easily accessible. As such, pornography is an ideal medium for examining representations of male and female orgasm. PornHub’s 50 most viewed videos of all time were viewed and coded for the frequency of male and female orgasm, orgasm-inducing sex acts (and whether activity inducing female orgasms included some form of clitoral stimulation), and auditory (verbal, vocal) and visual (bodily) indicators of orgasm. Content analysis was used to code and analyze the data. Results were analyzed in light of sexual script theory and previous orgasm research. Only 18.3% of women, compared to 78.0% of men, were shown reaching orgasm. Sex differences in depictions of orgasm, beyond the appearance of semen, were documented. Results support the male performance script as evident in pornographic depictions of orgasm, as well as coital and orgasm imperatives. As a result, representations of male and female orgasm in mainstream pornography may serve to perpetuate unrealistic beliefs and expectations in relation to female orgasm and male sexual performance.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; cours; discipline; orgasme; premier cycle; périodes historiques; rapports sociaux de sexe; représentation; ressource en ligne; sciences humaines; sex1911; sexologie; sexualité; thématiques